Dynamic subjectivity: implementation issues and computational reflection - Pryor, Jane (1998)
Subjectivity, and in particular dynamic subjectivity, is a desirable feature in programming languages, so as to allow the implementation of different views in order to enhance the reusability and integration of the key abstractions or components of these systems. This work presents a reflective meta-level architecture that supports dynamic subjectivity in an object-oriented system. This architecture has the advantage that the subjective behaviour is handled by a meta-level, such that the application that resides at the base level does not need to be modified.